Comportamiento de cuatro especies arbóreas proteícas y su efecto en el rendimiento de forraje en Zungarococha, Iquitos - Perú 2020 - Sinarahua Peña, Enoc (2022)
The research work was carried out at the National University of the Peruvian Amazon at the Faculty of Agronomy in the Cattle Project in the Zungarococha Farm, entitled "BEHAVIOR OF FOUR PROTEIN TREE SPECIES AND THEIR EFFECT ON FOOD YIELD IN ZUNGAROCOCHA, IQUITOS - PERU 2020. The evaluations were carried out 60 days after sowing with plots of 3 mx 1.2 m (3.6 m2) and an experimental area of 199.2 m2. With a Random Complete Block Design (DBCA), with four treatments and four repetitions, the treatments under study were: T1 (Morus nigra “MORERA”), T2 (Erythrina sp “AMASISA”), T3 (Tithonia diversifolia “GOLDEN BUTTON”) and T4 (Leucaena leucocephala “LEUCAENA”), obtaining the following results: With the T4 treatment (Leucaena leucocephala “LEUCAENA”) it was possible to increase the averages of plant height (m), green matter (gr / m2), dry matter (gr / m2) and the yields of green matter in Kg / plot and Kg / ha In this sense, it was shown that at least one of the doses of forage tree species has a favorable influence as a source of protein. According to what was found in this work, the doses of the forage tree species Leucaena leucocephala (LEUCAENA), influences as a protein source.